Active Force Control of a 5-link biped robot - Kwek, L. C.; Loo, Chu Kiong; Wong, E. K.; Rao, M. V. C.; Mailah, Musa (2004)
The performance of the biped system under the application of Active Force Control (AFC) is evaluated by making the biped walk on a, horizontal plane surface, In which the locomotion is constrained within the sagittal plane. The dynamic equations for a biped are nonlinear and highly coupled, and hence the biped does not perform well with the pure PD control. The effectiveness of the proposed method (Active Force Control with Crude Approximation-AFC-CA) is investigated and it is found that the system is robust and stable even under the influence of disturbances.